2021
DOI: 10.1021/acsaelm.1c00088
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Stable, Highly Conductive, and Mechanically Robust Metallized Textiles

Abstract: Textile-based wearable electronics, integrating the functions of electronics into the daily textiles, offers a comfortable interaction between humans and electronic devices. Production of highly conductive and environmentally stable textiles is the precondition for the ultimate wearable electronic system. However, due to the complicated porous structure, it is still technically challenging to endow textiles with desirable conductivity and stability, especially in the case of stretchable fabrics. Herein, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…A polymer-assisted ELD method was adopted in the design of metalized fabric to tackle the excessive rotation stress of the washing machine drum (1000 rpm). 253 The metalized fabric could maintain its low resistance even aer 100 min of continuous high-speed washing process. A highly washable EMI shielding cotton textile was designed through sequential Cu and superamphiphobic coatings.…”
Section: Ensuring the Standard Washer Environmentmentioning
confidence: 99%
“…A polymer-assisted ELD method was adopted in the design of metalized fabric to tackle the excessive rotation stress of the washing machine drum (1000 rpm). 253 The metalized fabric could maintain its low resistance even aer 100 min of continuous high-speed washing process. A highly washable EMI shielding cotton textile was designed through sequential Cu and superamphiphobic coatings.…”
Section: Ensuring the Standard Washer Environmentmentioning
confidence: 99%
“…To date, coated conductive fabrics have been extensively developed and reported in the literature, such as CNT‐coated cotton fabrics, [ 52 ] graphene‐coated fabrics, [ 53 ] Ag NWs‐coated cotton fabrics, [ 54 ] conducting polymer‐coated textiles, [ 55 ] and Ag‐/Ni‐/Cu‐coated textiles. [ 56 ] As only a thin layer of conducting materials is applied to the fabrics, coating usually does not affect the breathability and flexibility/stretchability of the fabrics. Hsu et al [54b] demonstrated a personal thermal management system by applying metallic NWs‐coated woven fabric ( Figure a).…”
Section: Strategies To Engineer Conductors Permeable Flexible and Stretchablementioning
confidence: 99%
“…In addition, the moisture permeability of the original fabric was not sacrificed, which was only reduced by 2% for Ag NWs coating (Figure 4b). Lu et al [56a] combined the electroless deposition and electrodeposition techniques for the fabrication of stretchable knitted fabric conductors (Figure 4c). Such a solution‐based process could achieve the loading of the conducting layer around individual fibers, thereby retaining the fibrous structure and corresponding comfort of the original textiles (Figure 4d).…”
Section: Strategies To Engineer Conductors Permeable Flexible and Stretchablementioning
confidence: 99%
See 1 more Smart Citation
“…Since textiles usually act as natural insulators, it is necessary for them to become conductive prior to electrodeposition. This is feasible by the creation of conductive layers (in a pre-treatment step) on a textile surface, using different metals, such as Ag [51,87], Cu, [88][89][90], Ni [91], Mxenes [92], Ni-Co selenide nanowires [93], NiMoO 4 /CoMoO 4 nanorods [94], LaMnO 3 /MnO nanoarrays, ZnO nanostructures deposited on an Ni-Cu-Ni conductive layer [95], and LiMn 2 O 4 [96], conductive polymers [97] or carbon-based materials [11,[22][23][24][25][26]. Schematic presentation of a typical electrochemical deposition process of a metallic layer onto PES fabric, using a three-electrode system, is shown in Figure 5a, where the deposition of Ni 3 Se 2 NPs is carried out on the conductive fabric (used as a working electrode), resulting in a metallic polyester layered fabric.…”
Section: Electrochemical Depositionmentioning
confidence: 99%